2006
DOI: 10.2460/javma.228.4.513
|View full text |Cite
|
Sign up to set email alerts
|

What Is Your Diagnosis?

Abstract: HistoryA 1-year-old sexually intact male mixed-breed dog was evaluated within an hour of being hit by an automobile. On physical examination, the rectal temperature was 38.5°C (101.2°F), the heart rate was 160 beats/min, and the respiratory rate was 60 breaths/min. Femoral pulses were weak and mucous membranes tacky. The dog was alert and responsive; both pupils were miotic, and conjunctival hemorrhage was detected in the right eye. Direct and indirect pupillary light reflexes were absent in the right eye. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…To the authors’ knowledge, traumatic AO luxation with survival has been reported in only eight dogs and one cat . The most common cause of dislocation is road traffic trauma, which was the cause in the case of the cat reported previously.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…To the authors’ knowledge, traumatic AO luxation with survival has been reported in only eight dogs and one cat . The most common cause of dislocation is road traffic trauma, which was the cause in the case of the cat reported previously.…”
Section: Discussionmentioning
confidence: 74%
“…AO luxation usually results in significant neurological injury with non‐specific clinical signs. In previous reported cases, gait dysfunction was present: ataxia, hemiparesis, tetraparesis and tetraplegia . Spinal reflexes were always increased.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Atlanto-occipital luxation is a rare condition in dogs and cats, because of the means of stability that prevent dislocation. Luxation and subluxation can occur in dogs and cats following trauma [ 2 , 4 , 5 , 10 , 11 , 14 , 17 , 18 ]. The stability of the atlanto-occipital joint is attributable to the multiple, strong ligaments associated with it [ 18 ].…”
mentioning
confidence: 99%